Analysis of states and Federal District actions for food and nutritional security in the Covid-19 pandemic in Brazil (Research, Society and Development, 2021)
The aim of this study was to analyze the proposals published by the state and Federal District governments to deal with food and nutritional insecurity during the COVID-19 pandemic in Brazil. By the documental analysis, were verified the official acts published by the states and the Federal District to mitigate food and nutritional insecurity. After searching and prior reading of the documents, a total of 55 acts, 31 (56.4%) decrees, 23 (41.8%) laws and 1 (1.8%) service order. It was found that 34 (61.8%) documents mentioned the articulation with municipalities to carry out actions in food and nutritional security and 37 (67.3%) acts mentioned intra or intersectoral actions. Predominated approaches involving school feeding, general aspects in food and nutritional security and distribution of staple basket food. There was a disparity in state and district actions, not only in number, but also in the scope and specificity of the proposals. Thus, it is important to institutionally strengthen and integrate the states and the Federal District in the management of food and nutrition security actions to guarantee the human right to adequate food.